2016
DOI: 10.1017/s0033291716003081
|View full text |Cite
|
Sign up to set email alerts
|

Affective lability mediates the association between childhood trauma and suicide attempts, mixed episodes and co-morbid anxiety disorders in bipolar disorders

Abstract: Our data suggest that affective lability may represent a psychological dimension that mediates the association between childhood traumatic experiences and the risk of a more severe or complex clinical expression of BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 51 publications
(66 reference statements)
5
63
0
Order By: Relevance
“…7,8 Despite these findings, research on MI in BD has been characterized by heterogeneity in the measures employed to define them (see Renaud and Zacchia 14 for a review) and other shortcomings, such as the use of self-reported measures [15][16][17][18] or the use of short-term follow-up periods, which may affect their reliability. 7,8 Despite these findings, research on MI in BD has been characterized by heterogeneity in the measures employed to define them (see Renaud and Zacchia 14 for a review) and other shortcomings, such as the use of self-reported measures [15][16][17][18] or the use of short-term follow-up periods, which may affect their reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Despite these findings, research on MI in BD has been characterized by heterogeneity in the measures employed to define them (see Renaud and Zacchia 14 for a review) and other shortcomings, such as the use of self-reported measures [15][16][17][18] or the use of short-term follow-up periods, which may affect their reliability. 7,8 Despite these findings, research on MI in BD has been characterized by heterogeneity in the measures employed to define them (see Renaud and Zacchia 14 for a review) and other shortcomings, such as the use of self-reported measures [15][16][17][18] or the use of short-term follow-up periods, which may affect their reliability.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Despite these findings, research on MI in BD has been characterized by heterogeneity in the measures employed to define them (see Renaud and Zacchia 14 for a review) and other shortcomings, such as the use of self-reported measures [15][16][17][18] or the use of short-term follow-up periods, which may affect their reliability. The aim of this study was to explore mood instability (MI) and subsyndromal symptomatology (SS) in a prospective cohort of OABD.…”
mentioning
confidence: 99%
“…Recently, studies have focused on examining the effects of childhood trauma on long‐term outcomes in individuals with BD, particularly CSA. Research has also shown that CSA is associated with affective lability, frequent mood episodes, substance abuse, and greater illness severity, all of which contribute to both increased suicidal ideation and attempts in BD (Aas et al., ; Du Rocher Schudlich et al., ). These associations are not surprising given that lifetime suicidality is significantly elevated in individuals with a history of childhood abuse and a BD diagnosis (McIntyre et al., ).…”
mentioning
confidence: 99%
“…Indeed, childhood traumatic experiences have been proposed as a major contributor to obesity in adulthood in several meta‐analyses . Interestingly, childhood trauma, especially emotional abuse, has been also associated with mixed episodes in patients with bipolar disorders . Altogether, it provides a potential framework to be tested in which childhood trauma would lead to both obesity and mixed features, and this warrants formal testing in mediation or moderation models.…”
mentioning
confidence: 99%
“…Altogether, it provides a potential framework to be tested in which childhood trauma would lead to both obesity and mixed features, and this warrants formal testing in mediation or moderation models. Furthermore, the effect of childhood trauma on mixed episodes in bipolar disorders is partly mediated by high levels of affective lability, a path that particularly involves emotional abuse and the affective lability anger domains . Affective lability, which is associated with both childhood trauma and mixed states, may also play a role when studying risk factors for obesity.…”
mentioning
confidence: 99%